Alternative Pavement Planning for Maros – Ujung Lamuru Road with the 2013 Bina Marga Method - Monalisa Bumbungan (Paulus Civil Engineering Journal, 2021)
This study aims to obtain the thickness of the flexible pavement (Flexible Pavement) from the Bina Marga 2013 method. The Bina Marga 2013 method is a method designed by the Directorate General of Highways, Ministry of Public Works. The change in the Bina Marga method to the Bina Marga 2013 method is intended to make the road pavement plan last longer. The Maros-Ujung Lamuru road section previously had a pavement layer where the old planning used the Component Analysis method and the author planned using the 2013 Bina Marga method.From the results of calculating the pavement thickness planning for the Maros - Ujung Lamuru section, segment 9 needs an increase in LPB 150 mm or 15 cm thick because the CBR value of the ground is low. Pavement thickness using the Bina Marga 2013 method is more economical and has a longer plan life than the Component Analysis method.